The effects of endoparasites on the reproductive performance of on-farm sheep in the Ethiopian highlands - Tekelye Bekele; Bruns, E.; Kasali, O.B.; Mutiga, E.R. (1993)
In 1988 and 1989, the effects of endoparasites on reproductive performance of on-farm sheep were studied at 5 sites in the Ethiopian highlands using nematode eggs per gram (EPG) counts, treamatode EPG and packed-cell volume (PCV). Mean litter size, lambing interval, annual reproductive rate and abortion rate were 1.04 to 1.33, 216 to 263 days, 1.7 to 2.1 and 1.3 to 6.5 percent, respectively, in different sites. Although, lambing interval and endoparasitism were significantly different at different sites, there was no significant differences in the level of endoparasitism affected body weights and body conditions scores of breeding ewes. Nursing ewes had more nematode and trematode EPG, low body weight and low body condition score compared with ewes during pregnancy and at lambing. This lactation-rise in EPG could be attributed to stress of suckling which reduced resistance.# percent